Experimental and Numerical Simulation Study on the Evolution Mechanism of Soil Plugging Effect of Pipe Piles - Sifeng Zhang; Chaonan Wang; Wei Fan; Jianyong Han; Qian Liu; Guozhang Ren (Advances in Civil Engineering)
To tackle the issue of relying solely on one research approach and the inadequate examination of the elements influencing the soil plug effect during the penetration of pipe piles, this study combines experimental modeling with numerical simulations. Through these approaches, we explore the formation and progression of the soil plug, delving into its underlying mechanisms from both macro and micro viewpoints. The findings indicate that as wall thickness decreases, tube diameter increases, inner wall roughness diminishes, and relative density of sand and soil rises, along with an uptick in pile sinking rates, the soil plug’s height within the pile increases. Conversely, the level of soil plug blockage decreases, leading to a weakened soil plug effect. Notably, soil layers characterized by higher hardness on top and lower softness beneath are more susceptible to soil plug occlusion. In contrast, configurations with softer upper layers and harder bases tend to provoke soil plug sliding. Furthermore, the static pressure pile sinking method typically results in a lower soil plug height relative to the hammering technique, making complete occlusion more likely to occur. Overall, the soil plug height is reduced with the static method, exhibiting a more pronounced effect compared to hammering, which is also more likely to lead to complete occlusion.